2009
DOI: 10.3389/neuro.04.008.2009
|View full text |Cite
|
Sign up to set email alerts
|

Temporal requirements of the fragile X mental retardation protein in modulating circadian clock circuit synaptic architecture

Abstract: Loss of fragile X mental retardation 1 (FMR1) gene function is the most common cause of inherited mental retardation and autism spectrum disorders, characterized by attention disorder, hyperactivity and disruption of circadian activity cycles. Pursuit of effective intervention strategies requires determining when the FMR1 product (FMRP) is required in the regulation of neuronal circuitry controlling these behaviors. In the well-characterized Drosophila disease model, loss of the highly conserved dFMRP causes c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(77 citation statements)
references
References 70 publications
6
70
0
Order By: Relevance
“…In accordance to previous data of other authors, we found that lack of dfmr1-expression caused an overgrown sLNV synaptic terminal area (dorsal projections), while its over-expression resulted in a retraction of the terminal synaptic branching and collapse of the synaptic area (22,36,43). These results are shown in Fig.…”
Section: Fig 3 Location Of a G-quartet-sequence In The 3'utr Of Dlgsupporting
confidence: 82%
See 1 more Smart Citation
“…In accordance to previous data of other authors, we found that lack of dfmr1-expression caused an overgrown sLNV synaptic terminal area (dorsal projections), while its over-expression resulted in a retraction of the terminal synaptic branching and collapse of the synaptic area (22,36,43). These results are shown in Fig.…”
Section: Fig 3 Location Of a G-quartet-sequence In The 3'utr Of Dlgsupporting
confidence: 82%
“…Both models confirm the main clinical aspects of FraX -neuronal features: dendrite and axon overgrowth and synaptic changes: increased spine numbers, abnormal synaptic growth, morphology and function, altered synaptic plasticity and circadian rhythms, as well as learning and memory deficits (3,22,33,40). Work on Drosophila has shown that dFMRP is also required for the normal neurite extension, guidance and branching of different neurons throughout the nervous system (16,36,34, reviewed in 59).…”
Section: Inroductionmentioning
confidence: 62%
“…Gatto and Broadie (2009) reported abnormalities in circadian clock circuits in dfmr1 mutant Drosophila, which were due to aberrant synaptic architecture and could be rescued by temporally controlled overexpression of dFMRP. In Fmr1 KO mice, dysregulated neuronal connectivity in the barrel cortex (Bureau et al, 2008) leads to defective glutamatergic synapse maturation, delayed and aberrant formation of sensory maps, and altered synaptic plasticity during the critical period (Harlow et al, 2010).…”
Section: Altered Neuronal Network Formation In Fxsmentioning
confidence: 99%
“…,UAS-9557-3/TM6 line (a wild-type dfmr1 transgene under UAS control; Gatto and Broadie, 2009), with progeny raised at the permissive temperature (18°C) until the last pupal day of development (pupal day 4, P4). At P4, animals were shifted to the restrictive temperature (29°C) until day 1 post eclosion, thereby releasing Gal80 inhibition and activating dfmr1 expression in targeted neurons.…”
Section: Mmentioning
confidence: 99%
“…For optogenetic manipulations, UAS-ChR2(H134R)-mCherry generously provided by Leslie Griffith (Pulver et al, 2009) and UAS-eNpHR3.0-EGFP (this study, see below) were introduced using standard genetic techniques. For conditional dfmr1 manipulation, UAS-dfmr1-RNAi (TRiP, Harvard) and a wild-type dfmr1 rescue construct (UAS-9557-3; Gatto et al, 2009) were crossed into control and mutant backgrounds, with all progeny raised at the permissive temperature (18°C) until pupal day 4 (P4), and then shifted to the restrictive temperature (29°C). These experiments involved the following sets of parental pairings: (1) tubP-Gal80ts/CyO;dfmr1…”
Section: Drosophila Geneticsmentioning
confidence: 99%